Saccharide Characteristics and Their Potential Health Effects in Perspective - Brouns, Fred (Frontiers in Nutrition, 2020)
To understand the effects of saccharides on our metabolism and health, we need a clear understanding of what they are, how they differ, and why some types are deemed “less healthy” and others “better for health.” There are various ways to look at this topic. Firstly, saccharides can be classified according to their degree of polymerization (DP). This classification is useful when qualitative or quantitative analysis and calculation of intakes are required or for food-labeling definitions. However, it does not account for the fact that saccharides with a similar DP can differ in molecular composition, which will influence digestion, absorption, and metabolism. Secondly, another approach widely used in the biomedical and nutritional sciences is therefore a physiological classification, which addresses the rate and degree of digestibility and absorption, the glycemic response, and the metabolic fate. The individual health status also plays a role in this respect. An active, lean person will have a metabolic response that differs from an inactive person with overweight and insulin resistance. However, this approach will not give a complete answer either because the characteristics of the matrix/meal in which these carbohydrates (CHOs) are present will also influence the responses of our body. Thirdly, one can also rank CHOs by comparing their functional/technological properties, such as relative sweetness, viscosity, and solubility. Understanding CHO characteristics and related physiological responses will help understand health and disease implications. Therefore, a brief outline of different carbohydrate classifications is presented. This outline will be placed in the context of potential overall effects after consumption. The answer to the question whether we should we eat less of certain sugars depends on the angle from which you look at this matter; for example, do you address this question from a single molecular characteristic point of view or from a meal quality perspective? Looking at one particular CHO characteristic will almost always lead to a different conclusion (e.g., the labeling of fructose as toxic) than evaluating from a “total perspective” (fructose has adverse effects in certain conditions). Examples are given to help understand this matter for the benefit of justified dietary/food-based recommendations.